2017
DOI: 10.1155/2017/6793456
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Cell Cycle Arrest and Apoptotic Response of Head and Neck Squamous Carcinoma Cells (Detroit 562) by Caffeic Acid and Caffeic Acid Phenethyl Ester Derivative

Abstract: Natural polyphenols have been observed to possess antiproliferative properties. The effects, including apoptotic potential of bioactive phenolic compounds, caffeic acid (CA) and its derivative caffeic acid phenethyl ester (CAPE), on cell proliferation and apoptosis in human head and neck squamous carcinoma cells (HNSCC) line (Detroit 562) were investigated and compared. Cancer cells apoptosis rates and cell cycle arrests were analysed by flow cytometry. Exposure to CA and CAPE was found to result in a dose-dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 57 publications
4
21
0
1
Order By: Relevance
“…These results correlate with those of Yu et al [45], which demonstrated the ability of CAPE activate caspase-3 and induce apoptosis in YD15, HSC-4 and HN22 cells. Similar results were obtained by Kabała-Dzik et al [46] and Dziedzic et al [47]; CAPE successfully induced apoptosis after 24 h incubation in MDA-MB-231 and NHSCC cell lines. In our work, HT29 was the most resistant to CAPE, which may be due to a mutation in the p53 gene affecting their resistance to apoptosis.…”
Section: Discussionsupporting
confidence: 88%
“…These results correlate with those of Yu et al [45], which demonstrated the ability of CAPE activate caspase-3 and induce apoptosis in YD15, HSC-4 and HN22 cells. Similar results were obtained by Kabała-Dzik et al [46] and Dziedzic et al [47]; CAPE successfully induced apoptosis after 24 h incubation in MDA-MB-231 and NHSCC cell lines. In our work, HT29 was the most resistant to CAPE, which may be due to a mutation in the p53 gene affecting their resistance to apoptosis.…”
Section: Discussionsupporting
confidence: 88%
“…Studies have shown that CA has various pharmacological activities, including anti-inflammatory, antioxidant, and immunomodulatory activities [7][8][9]. CA also exhibits an anti-cancer effect against human cervical carcinoma, head and neck squamous carcinoma, colon cancer, and renal carcinoma [12][13][14]26]. A previous study showed that CA promoted NSCLC A549 cell proliferation and enhanced PTX-induced proliferation inA549 cells [17], suggesting that it has the potential to facilitate A549 growth through the p53 pathway and enhance the protective effect of PTX.…”
Section: Discussionmentioning
confidence: 99%
“…The results also support other previously reported studies of the potential of caffeic in inducing apoptosis in cancer cells. (8,11) In the complex mechanism of apoptosis, caspase plays a very crucial role. In the present study, we found a significant difference in the number of apoptotic cells between caffeic acid-treated group and Z-VAD-pretreated group (p<0.05), in which the percentage of apoptotic cells was lower in the Z-VAD pretreated group.…”
Section: Discussionmentioning
confidence: 99%
“…(4)(5)(6) Caffeic acid significantly reduces the activity of nuclear factor κB (NFκB), a cell signaling pathway involved in osteoclastogenesis (5), in which NFκB inhibition can cause tumor cells to stop proliferating or becoming more sensitive to the actions of anti-tumor agents. (7) Caffeic acid and related polyphenolic compounds today attract much special attention because of its ability to protect the human body from oxidative stress that can lead to cancer (8), aging (9), and cardiovascular disease (10). A previous study has shown that caffeic acid can induce apoptosis in MG63 osteosarcoma cells and show the presence of caspase-8, -9 and -3 in the induction of apoptosis.…”
Section: Introductionmentioning
confidence: 99%